First trimester serum tests for Down's syndrome screening - Alldred, S. Kate; Takwoingi, Yemisi; Guo, Boliang; Pennant, Mary; Deeks, Jonathan J.; Neilson, James P.; Alfirevic, Zarko (Wiley, 2015)
Background